Absorption of Dilute Sulfur Dioxide in Aqueous Poly-Ethylene Glycol 200 Solutions at 298.15 K and 122.60 kPa - Zhang, Jianbin; Zheng, Yan; Wu, Shijun; Hu, Yuqiang; Yan, Ligang (Asian Journal of Chemistry, 2012)
In present work, isothermal gas-liquid equilibrium (GLE) data are measured for the absorption of dilute SO2 in various aqueous poly-ethylene glycol 200 (PEG) solutions at 298.15 K and 122.60 kPa and SO2 partial pressures in the range of (0.8-127) Pa. Measurements were carried out by a saturation method using a glass absorption apparatus, which were controlled at constant temperature using a thermostatic circulation bath with a Beckmann thermometer. The gas-liquid equilibrium data were measured with relative uncertainties within ± 0.02 K for temperature, ± 0.133 kPa for total pressures, ± 0.6 % for SO2 concentration in the liquid phase and ± 3.5 % for SO2 volume fraction in the gas phase. The measurement showed that the solubility of SO2 in the system PEG (1) + water (2) increased with increasing PEG concentration in the mass fraction range of w1 = (0.60-1.00) and the solubility of SO2 in the PEG (1) + water (2) system presented a minimum at the mass fraction of w1 = 0.60 of 101 mg dm-3 when SO2 in the gas phase is designed at FSO2 = 5 × 10-4. The peculiarity of this work is used to provide important gas-liquid equilibrium data for the design and operation of the absorption and desorption processes in flue gas desulfurization with potential industrial application of various aqueous solutions of poly-ethylene glycol 200.